Урожайність сорго залежно від способів сівби в Степу України - Татаринов, Рустам Рустамович; Tatarynov, Rustam (ЦНТУ, 2025)
В даній кваліфікаційній роботі вивчено вплив способів сівби на продуктивність посівів сорго. Мета досліджень – вивчити оптимальні способи сівби в посівах сорго. Встановлено, що застосування широкорядного посіву позитивно відображається на онтогенезі сорго та сприяє підвищенню урожайності його посівів в умовах Степу України. This qualification work examines the influence of sowing methods on the productivity of sorghum crops. The purpose of the research is to study the optimal sowing methods in sorghum crops. It has been established that the use of wide-row sowing has a positive effect on the ontogenesis of sorghum and contributes to increasing the yield of its crops in the conditions of the Steppe of Ukraine.
Sorghum productivity depending on sowing methods in the Steppe of Ukraine
Keywords: сорго; способи сівби; врожайність; sorghum; sowing methods; yield